PARASITISM OF MATHEVOTAENIA SP. (CESTODA: ANOPLOCEPHALIDAE) AND CENTRORHYNCHUS SP. (ACANTHOCEPHALA: CENTRORHYNCHIDAE) IN DASYPUS NOVEMCINCTUS (MAMMALIA: XENARTHRA) IN BRAZIL - Nunes Gomes, Samara (2012)
During the period of 2009 and 2010, 30 specimens of Dasypus novemcinctus (Linnaeus, 1758) were collected from different regions of the state of Rio Grande do Sul, Brazil, with the objective of identifying the parasites that occurs in the Pampa Biome. Cestoda and Acanthocephala, were found in the intestine of six armadillos, which were identified as Mathevotaenia sp. (Cestoda: Anoplocephalidae) and Centrorhynchus sp. (Acanthocephala: Centrorhynchidae). Both parasites are recorded for the first time in nine banded armadillo in Brazil.